Bacteroides ovatus-derived N-methylserotonin inhibit colorectal cancer via the HTR1D-mediated cAMP-PKA-NF-κB signaling axis - He, Jikai; Jia, Jiaqi; Qu, Wenhao; Zhang, Shuyu; Fan, Keyu; Lin, Runze; Zhao, Wei; Niu, Yan; Huang, Yanqiang; Jia, Lizhou (Frontiers in Immunology, 2025)
ObjectiveTo analyze differences in gut microbiota composition, metabolites, and metabolic pathways between healthy individuals and colorectal cancer (CRC) patients, and to investigate the inhibitory effects of N-methylserotonin (NMS) produced by Bacteroides ovatus (B.o) from orange fiber on CRC progression and its underlying mechanisms.Methods(1) Fecal samples from CRC patients (n=26) and healthy controls (n=20) were collected for metagenomic sequencing and untargeted metabolomics analysis; (2) The ability of B.o to produce NMS from orange fiber was validated in vitro; (3) A CRC mouse model was established using azoxymethane (AOM)/dextran sulfate sodium (DSS) induction, followed by evaluation of body weight, rectal bleeding, colorectal length, tumor number, and intestinal barrier function; (4) Network pharmacology, molecular docking, and western blot analysis were combined to verify the mechanism of action; (5) 16S rRNA sequencing was performed to analyze gut microbiota changes.Results(1) CRC patients showed significantly increased metabolic pathways including glycolysis, methane metabolism, beneficial amino acid degradation, and linoleic acid degradation, along with significantly decreased B.o abundance and NMS levels, which were positively correlated; (2) NMS significantly inhibited CRC cell proliferation, migration, and invasion, while promoting apoptosis; (3) Combined treatment with B.o and orange fiber or NMS alone reduced tumorigenesis and improved intestinal barrier function; (4) Mechanistic studies revealed that these effects could be mediated through downregulation of 5-hydroxytryptamine receptor 1D (HTR1D) expression and inhibition of the cAMP/PKA/IκBα/NF-κB pathway; (5) The treatments optimized gut microbiota structure and metabolite composition.ConclusionB.o and its metabolite NMS possibly inhibit CRC progression by modulating the HTR1D-mediated cAMP/PKA/NF-κB signaling pathway, while improving gut microbiota structure, providing a novel therapeutic target for CRC prevention and treatment.